Towards inclusive growth in Africa: Remittances, and financial development interactive effects and thresholds - Isaac Kwesi Ofori; Emmanuel Y. Gbolonyo; Toyo Amegnonna Marcel Dossou; Richard Kwabena Nkrumah; Emmanuel Nkansah (African Governance and Development Institute (AGDI), 2023)
The study employs macro data for 42 African countries to examine the interactive and threshold effects of financial development in the remittances-inclusive growth relationship. First, evidence based on the system GMM estimator shows that remittances are not statistically significant in promoting inclusive growth in Africa. Notably, across the economic growth and income inequality dimensions of inclusive growth, we find that although remittances are ineffective in boosting the former, they deepen the latter. Second, we find that Africa's underdeveloped financial sector dampens the marginal positive effect of remittances on inclusive growth. Third, our threshold analysis indicates that for financial development to interact with complementary policies to foster inclusive growth in Africa, a minimum threshold of 14.5% is required. We conclude by informing policy on the level of investments needed for financial development to promote fairer income growth and distribution in Africa.
Keywords: F22; F24; G21; I3; N27; O11; O55; 330; Africa; Financial Development; Inclusive Growth; Income Inequality; GMM; Remittances